Genetic diversity of the pan-European freshwater mussel Anodonta anatina (Bivalvia: Unionoida) based on CO1: new phylogenetic insights and implications for conservation - Froufe, Elsa (2015)
1. The duck mussel, Anodonta anatina, has been described as abundant and widespread in Europe. However, it is listed as near threatened or threatened in several countries owing to severe declines in abundance and/or spatial distribution. 2. Despite its potential ecological importance and conservation status almost nothing is known regarding its genetic diversity. 3. As a preliminary analysis, variation within the cytochrome oxidase 1 mitochondrial gene was determined from European specimens from Portugal in the south west, to Ukraine in the east, and Sweden in the north. 4. Three major mtDNA clades were retrieved: clade 1 includes all the individuals from Iberia, except those from the Ebro basin; clade 2 includes all the European non-Iberian and non-Italian samples; and clade 3 includes all the individuals from Italy and from the Ebro basin. AMOVA analysis revealed significant genetic differences among the three clades. Within each of the major clades, several geographically related haplogroups were also retrieved, especially in Iberia, where four genetically distinct groups (North-West, South-Central, South-West and Ebro) were revealed. 5. Given the evidence of regional declines of A. anatina in Europe, the confirmation of geographically distinct genotypes indicates a need for the development of management strategies directed towards the conservation of localized populations.